An Exploration of Students’ Foreign Language Anxiety in English Classroom - Hidayat, Didin Nuruddin; Hasanah, Uswatun; Eviyuliwati, Ismalianing; Septiawan, Yudi (FKIP Universitas Lampung, 2022)
An Exploration of Students’ Foreign Language Anxiety in English Classroom. Objectives: This study aims to investigate students’ foreign language anxiety in English class: students’ anxiety levels, students’ anxiety kinds, and students’ attitudes toward English class. Methods: This study used a quantitative approach and a survey method with a descriptive research design. Findings: The findings of the study showed 62.5% of the students felt anxious in foreign language level sequenced from mildly anxious, anxious, and very anxious. Students’ dominant kind of foreign language anxiety was fear of negative evaluation. Finally, more than half of the students had negative attitudes toward English class. Meanwhile, the rest of the students showed positive attitude. Conclusion: In conclusion, most of the students feel anxious in English class. They mostly experience anxiety due to the negative evaluation, and their attitudes toward English class could not completely determine their foreign language anxiety level. Keywords: foreign language anxiety, English classroom, students’ attitudes.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202213